2002
DOI: 10.1583/1545-1550(2002)009<0665:awsatt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Wall Stress and Tendency to Rupture Are Features of Physical Wall Properties: An Experimental Study

Abstract: AAA wall mechanics contribute more significantly to peak wall stress than pressure variations within the system. In particular, increased stiffness (analogous to collagen deposition) significantly increased peak wall stress, which was located at the inflection point rather than at the maximum diameter. Techniques to measure the AAA wall mechanics and the rate of deterioration may predict AAA rupture in the untreated state or in the presence of an endoleak following endovascular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…A recent experimental study using a compliant polymer as an arterial representation showed that the value of PWS in the presence of systemic pressurization or endoleak reached only a very small percentage of the material failure strength. 14 In this AAA model with a reinforced wall, the peak stress was significantly greater, and wall strength contributed more significantly to wall stress than increasing pressurization within the AAA sac. The authors proposed that AAA wall mechanics could theoretically contribute more significantly to PWS than pressure variations within the system.…”
Section: Role Of Aortic Wall Strengthmentioning
confidence: 85%
“…A recent experimental study using a compliant polymer as an arterial representation showed that the value of PWS in the presence of systemic pressurization or endoleak reached only a very small percentage of the material failure strength. 14 In this AAA model with a reinforced wall, the peak stress was significantly greater, and wall strength contributed more significantly to wall stress than increasing pressurization within the AAA sac. The authors proposed that AAA wall mechanics could theoretically contribute more significantly to PWS than pressure variations within the system.…”
Section: Role Of Aortic Wall Strengthmentioning
confidence: 85%
“…This questions the theory that rupture simply occurs at the point of maximum mechanical stretch where the diameter is greatest [58]. Diameter was first used in 1966 to predict AAA at high risk of rupture and has since been modified in the light of experience and more accurate imaging [59].…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Diameter was first used in 1966 to predict AAA at high risk of rupture and has since been modified in the light of experience and more accurate imaging [59]. The simple observation that not all AAAs rupture at a specific diameter indicates that other patient-specific and aneurysm-specific variables may have an effect, for example: obstructive lung disease, smoking, hypertension, a widened pulse pressure, the ratio of the aneurysm diameter to the diameter in the adjacent normal aorta, and aortic wall tension [58]. Presently, it is not possible to obtain exact peak wall stress or accurate local wall strength measurements.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Because of our fast-aging society, this is a problem calling for immediate attention. Previous studies have reported cardiovascular diseases to be closely related to blood flow [1][2][3][4][5] , and much research has been performed from this point of view, most of which has been carried out by experimental measurement [6][7][8][9][10] (in vitro and in vivo) or, recently, by computational fluid dynamics (CFD). Even with substantial improvement in measurement technology, it is still difficult to accurately measure the detailed structure of 3D blood flow, including the vessel wall shear stress and the wall pressure, important factors of cardiovascular diseases, by using existing measurement techniques, such as MRI, CT, X-ray, and ultrasonic measurement.…”
Section: Introductionmentioning
confidence: 99%